Analysis of QOS VLAN Based on Djikstra’s Algorithm on Open Shortest Path First(OSPF) - Muhammad Nur Alfani; Bambang Sugiantoro (IJID (International Journal on Informatics for Development), 2018)
As an institution engaged in SMK Muhammadiyah 03 Yogyakarta requires network infrastructure as a medium of communication. Infrastructure in SMK Muhammadiyah based VLAN but still using static routing and star topologies as a medium of communication between router. This leads to the main router performance overburdened  which makes the network infrastructure down. It is necessary to reform the network, especially in the communication protocol on the router by using protocol Open Shortest Path First(OSPF). OSPF is a link state-based routing protocol that uses Dijkstra’s algorithm to find the best path is taken as a communication medium. Makin paths made by considering various aspects of the parameters that affect network traffic. OSPF can minimize down on network infrastructure caused by the buren of a huge traffic to maintain the stability of traffic on communication lines. The results using the method QOS on infrastructure with the OSPF protocol can be classified very nice. It is obtaine from the measurement parameter delay <150 ms, packet loss (0%), an bandwidth has a very goo category based on the standard TIPHON. From the results of the QOS parameters also obtained a decrease in delay value by 31% on infrastructure with the OSPF protocol. This proves that the network traffic is more stable when using OSPF protocol.